A multi-dimensional approach for accepting and using e-learning cloud: a developing country's perspective. Issue 2 (2nd March 2022) - Alshaher, Ali; Hasan, Mohammed Mustafa Hussein; Abdulmuhsin, Amir A.
The study investigates the issues on the acceptance and use of e-learning computing to propose appropriate solutions. This research was conducted by proposing a multi-dimensional model to influence the recipient's intention to accept and use cloud computing. The study variables were analysed using a quantitative approach, which included determining the validity of theoretical trends as well as the study hypotheses. Selected colleges of the universities of a middle eastern country were investigated for this study. Questionnaires were distributed among 375 students, and 369 of these questionnaires were retrieved. Ultimately, the sample size included 361 participants. The researchers used statistical data processing by SPSS, Amos and SmartPLS. The results of this study showed evidence of the crucial role of the proposed model in the acceptance and use of cloud computing e-learning.